A novel approach for a 2D/3D image registration routine for medical tool navigation in minimally invasive vascular interventions - Schwerter, Michael; Lietzmann, Florian; Schad, Lothar R. (Zeitschrift für medizinische Physik, 2016)
Minimally invasive interventions are frequently aided by 2D projective image guidance. To facilitate the navigation of medical tools within the patient, information from preoperative 3D images can supplement interventional data. This work describes a novel approach to perform a 3D CT data registration to a single interventional native fluoroscopic frame. The goal of this procedure is to recover and visualize a current 2D interventional tool position in its corresponding 3D dataset. A dedicated routine was developed and tested on a phantom. The 3D position of a guidewire inserted into the phantom could successfully be reconstructed for varying 2D image acquisition geometries. The scope of the routine includes projecting the CT data into the plane of the fluoroscopy. A subsequent registration of the real and virtual projections is performed with an accuracy within the range of 1.16±0.17mm for fixed landmarks. The interventional tool is extracted from the fluoroscopy and matched to the corresponding part of the projected and transformed arterial vasculature. A root mean square error of up to 0.56mm for matched point pairs is reached. The desired 3D view is provided by backprojecting the matched guidewire through the CT array. Due to its potential to reduce patient dose and treatment times, the proposed routine has the capability of reducing patient stress at lower overall treatment costs.
Gesehen am 19.02.2019
Available online 2 May 201